PENYEMPURNAAN PENGUKURAN KONTRIBUSI PARIWISATA: ALTERNATIF PERCEPATAN PERTUMBUHAN EKONOMI INDONESIA - Mun'im, Akhmad (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
The United Nations World Tourism Organization (UNWTO) recommends International Recommendations for Tourism Statistics (IRTS) and Tourism Satellite Accounts: Recommended Methodological Framework (TSA: RMF) 2008 as standard manuals for calculating tourism contributions to the Gross Domestic Product (GDP). The Statistics Indonesia-BPS, as a national statistical office in Indonesia, adopted these recommendations in measuring tourism contribution in Indonesia. So, it manages in comparison with a global level. This adoption also improves the method of calculating tourism contributions conducted previously using a shock approach in the input-output table to a supply-demand by using the supply and use table (SUT) framework. The SUT framework arranges the provision of tourism products produced by the tourism and non-tourism industries. By juxtaposing it with internal tourism consumption, the tourism contribution is achieved. The calculation results show an increasing trend of Indonesia's tourism contribution from 2016 to 2019. Judging from the tourism direct gross domestic product (TDGDP), the tourism sector contributes 4.6 to 4.9 percent of the Indonesian GDP.